WebGIS-Based Land Asset Visualization (Case Study: Pangkep Regency Government) - Rizal H, Muhammad; Ratnawati, Ratnawati; Rahman, Abd.; Masyhur, Mahfudz; Warni, Elly (International Journal of Informatics, Economics, Management and Science, 2024)
This study discusses the implementation of e-Government in Pangkep Regency with the aim of improving public services, especially in land asset management. This research responds to requests from the Department of Housing, Settlement Areas and Land (Disperkimtan) by addressing the challenges of complex administrative procedures and increasing public awareness of land asset management. The goal is to design a web-based Land Asset Mapping Information System using WebGIS to simplify administrative processes and increase transparency. This research applies the Rapid Application Development (RAD) method. The results show an effective user interface (UI) in land certificate creation as well as smooth functions in the login and land acquisition process. This system is able to handle user loads well, which is reflected in the user satisfaction rate of 76.4%.